ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROPORSI PESERTA KELUARGA BERENCANA (KB) AKTIF DAN FERTILITAS DI KABUPATEN/KOTA PROVINSI BALI - Rismha Dwi Sukma Yoni, Sang Ayu Ade; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The aims of this study were: 1) to analyze the effect of education level, poverty, and government spending on the proportion of active family planning participants 2) to analyze the effect of education level, poverty, government spending and the proportion of active family planning participants on fertility 3) to determine the indirect effect of education level, poverty, government spending on fertility through the proportion of active family planning participants. This research was conducted in the regency/city of Bali Province which consists of 8 regencies and 1 city. The data analysis technique used in this research is path analysis. The results showed that 1) the proportion of the poor had a negative and insignificant effect on the proportion of family planning participants while the percentage of the poor had a positive and significant effect on fertility, 2) the level of education and government expenditures had a positive and significant effect on the proportion of family planning participants but the level of education and education expenditures the government has a negative and significant effect on fertility, 3) the proportion of active family planning participants can mediate the variables of the poor population, education level and government spending on fertility.